MDM2 inhibition is associated with the emergence of TP53-altered clonal hematopoiesis - Vishesh Khanna; Gohar Eslami; Rochelle Reyes; Robert Diep; Sebastian Fernandez-Pol; Henning Stehr; Carlos Jose Suarez; Harlan Pinto; James M. Ford; Tian Yi Zhang; Christopher T. Chen (npj Precision Oncology)
Abstract Murine double minute 2 (MDM2) inhibitors have shown promising activity in TP53-wild type tumors and are under active investigation across a spectrum of malignancies. Herein, we report a 51-year-old female with MDM2-amplified, TP53-wild type adenoid cystic carcinoma who was treated with a MDM2 inhibitor and developed persistent pancytopenia despite drug discontinuation. Her pancytopenia was associated with 20 distinct pathogenic TP53 mutations in peripheral blood and bone marrow not present in drug-resistant tumor tissue. Plasma TP53 mutations were similarly detected among 4 other patients treated at our institution, with the number of mutations correlating strongly with duration of treatment. This case suggests that MDM2 inhibitors are associated with TP53 clonal hematopoiesis, which may confer a risk of subsequent myeloid malignancy. As multiple MDM2 inhibitor trials are ongoing, our findings underscore the need for further investigation into the potential long-term deleterious effects of these inhibitors in the hematopoietic stem and progenitor compartment.